(untitled) (Revista Ciência Agronômica, 2015)
The use of organic waste from industrial processes in agriculture is a strategy not only for improving soil properties but also for promoting the utilization of recycled nutrients by market crops and for reducing environmental impact. The aim of this study was to evaluate the effects of using organic waste from pork and poultry slaughterhouses (OWS) applied alone or in combination with mineral fertilizer (MF) on the dynamics of soil organic matter (SOM) compartments. The experimental design adopted was that of completely randomized blocks with six treatments and three replicates. The treatments consisted of a general control (T1) without the addition of MF and OWS, the application of MF alone at 100% of the recommended fertilizer levels for the crops (T2),the application of OWS alone at a fixed dose of 2 Mg ha-1 (T3), and the following three combinations of MF and OWS: 75% MF + 25% OWS (T4); 50% MF + 50% OWS (T5); and 25% MF + 75% OWS (T6). The application of OWS promoted increase in the labile fractions extracted by potassium permanganate (C-OXP) and hot water (C-HW) compared with using MF alone. Using OWS in the combination of 50% MF + 50% OWS increased the content and stock of total organic carbon (TOC) in the 0-20 cm layer and of particulate organic C (POC) and C-OXP in the 0-5 cm layer.